Examining the impact of L2 proficiency and keyboarding skills on scores on TOEFL-iBT writing tasks. (April 2014) - Barkaoui, Khaled
A major concern with computer-based (CB) tests of second-language (L2) writing is that performance on such tests may be influenced by test-taker keyboarding skills. Poor keyboarding skills may force test-takers to focus their attention and cognitive resources on motor activities (i.e., keyboarding) and, consequently, other processes and aspects of writing (e.g., planning, revising) might be left unattended to, which can lead to poor text quality and lower test scores. Such effects might be more pronounced for L2 test-takers. This study investigated the impact of keyboarding skills on test-takers' scores in the context of the TOEFL-iBT Writing Section. Each of 97 test-takers, with different levels of English language proficiency (low vs. high) and keyboarding skills (low vs. high), responded to two TOEFL-iBT writing tasks (independent and integrated) on the computer. Test scores were statistically compared across tasks and test-taker groups. The findings indicated that overall English language proficiency and writing ability in English contributed substantially to variance in task scores, while keyboarding skill had a significant, but weak, effect on task scores. Additionally, keyboarding skills effects depended on task type. While these findings support the claim that performance on TOEFL-iBT writing tasks depends mainly on test-taker English language proficiency, they also raise important questions about the relationships between keyboarding skills, L2 writing ability, and performance on CB L2 writing tests, as well as factors affecting these relationships.